ACCIDENTS IN SURGERY. ALGORITHM OF ACTIONS. MEDICAL COLLECTION, LOG ENTRY, PERSONAL PROTECTIVE EQUIPMENT FOR MEDICAL PERSONNEL - Мухамадиева Камола Дилшод қизи; Юсупов Ҳамза Сафарович (Web of Journals Publishing, 2024)
Specialists working in the surgical field of medicine (surgeons, dentists, gynecologists, resuscitators...) directly communicate with patients with disorders of the skin and mucous membranes and the blood coming out of them; this patient’s blood contains VG “B”. , AIDS and other hematogenous infections transmitted through blood. A healthcare worker can become infected with these infections during a medical accident. Relevance and purpose of the topic: Reducing emergencies and preventing occupational injuries among medical workers.
Keywords: Emergency medical care, algorithm of first aid actions in emergency conditions, First aid kit for emergency parenteral infection. Personal protective equipment for medical workers.